2013
DOI: 10.1158/1535-7163.mct-12-0737
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphorylated PEA-15 Sensitizes Ovarian Cancer Cells to Paclitaxel by Impairing the Microtubule-Destabilizing Effect of SCLIP

Abstract: Paclitaxel is a standard chemotherapeutic agent for ovarian cancer. PEA-15 (phosphoprotein enriched in astrocytes-15 kDa) regulates cell proliferation, autophagy, apoptosis, and glucose metabolism and also mediates AKT-dependent chemoresistance in breast cancer. PEA-15's functions are tightly regulated by its phosphorylation status at Ser104 and Ser116. However, the effect of PEA-15 phosphorylation status on chemosensitivity of cancer cells remains unknown. Here, we tested the hypothesis that PEA-15 phosphoryl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Interestingly, the OVTOKO ovarian cancer cell line is highly resistant to paclitaxel and can be sensitized to the drug by increasing MT stability via inhibition of the MT-stabilizing protein SCLIP. 22 The potential therapeutic applications of this discovery include consideration of strategies such as sequential or concurrent use of such MT-stabilizing protein inhibitors with other drugs in patients with paclitaxel-resistant ovarian cancers. This finding provides opportunity for further studies to investigate this potential novel avenue.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the OVTOKO ovarian cancer cell line is highly resistant to paclitaxel and can be sensitized to the drug by increasing MT stability via inhibition of the MT-stabilizing protein SCLIP. 22 The potential therapeutic applications of this discovery include consideration of strategies such as sequential or concurrent use of such MT-stabilizing protein inhibitors with other drugs in patients with paclitaxel-resistant ovarian cancers. This finding provides opportunity for further studies to investigate this potential novel avenue.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that PEA-15 levels were significantly reduced in breast tumor tissues compared to their normal counterparts. The function of PEA-15 as tumor suppressor or as inhibitor of tumor cell growth and invasion in various cancers has been investigated[8; 9; 17; 18]. Our group and others reported that phosphorylation status of PEA-15 is associated with the anti-tumor functions of PEA-15.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, we proposed that unphosporylated-PEA-15 at both Ser104 and Ser116 could result in more potent suppression of tumorigenicity than wild-type PEA-15 in breast cancer. We have shown that the double-unphosphorylated form (PEA-15-AA), strongly inhibited tumor growth and Ki-67 expression in an ovarian cancer xenograft model[8; 9]. Several other studies also have shown that unphosphorylated form of PEA-15 acts as a tumor suppressor in cervical cancer and lung cancer cells [26; 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas phosphorylated PEA‐15 has a negligible inhibitory effect on the function of ERK2, non‐phosphorylated PEA‐15 is known to directly bind to ERK2 and block its functions, such as substrate binding and nuclear translocation (Callaway, Abramczyk, Martin, & Dalby, ; Krueger, Chou, Glading, Schaefer, & Ginsberg, ; Trencia et al, ). With such a function, PEA‐15 itself has gained significant attention as a potential therapeutic for cancer treatment (Lee et al, ; Xie et al, ; Xie et al, ). The development of PEA‐15 as a therapeutic agent has several barriers, however, such as a low binding affinity (∼3.4 μM) for ERK2 and the lack of an efficient intracellular delivery system (Mace et al, ).…”
Section: Introductionmentioning
confidence: 99%